The Use of Smartphone in Improving the Students’ Speaking Skill - Paiman Paiman; Audi Yundayani; Suciati Suciati (STAI Hubbulwathan Duri, 2022)
Technology has already had a significant impact on many aspects of life, including education. As a learning tool, the Smartphone has become indispensable for system implementation. The study's goal is to investigate how smartphones can assist students in improving their public speaking skills. The study employed classroom action research in three cycles. This study included 39 second-grade students from a junior high school in West Java. Interviews, observations, and questionnaires were used to collect qualitative data. Furthermore, quantitative data from speaking tests were obtained. According to the findings of this study, using a smartphone during a course activity can keep students' attention and interest. They also gained the confidence to speak up and actively participate in class. Furthermore, smartphones help students stay engaged while learning. The speaking test results revealed that the students' speaking abilities had improved. The mean score for students in cycle one was 70.4, 77.6 in cycle two, and 82.2 in cycle three. As a result, because smartphones are compatible with student characteristics, they can be used as a learning media to assist students in improving their speaking skills, broadening their knowledge, and developing their other English practice.